2023
DOI: 10.1021/acschembio.3c00498
|View full text |Cite
|
Sign up to set email alerts
|

Rieske Oxygenase-Catalyzed Oxidative Late-Stage Functionalization during Complex Antifungal Polyketide Biosynthesis

Florian M. Guth,
Frederick Lindner,
Simon Rydzek
et al.

Abstract: Rieske oxygenases (ROs) from natural product biosynthetic pathways are a poorly studied group of enzymes with significant potential as oxidative functionalization biocatalysts. A study on the ROs JerL, JerP, and AmbP from the biosynthetic pathways of jerangolid A and ambruticin VS-3 is described. Their activity was successfully reconstituted using whole-cell bioconversion systems coexpressing the ROs and their respective natural flavin-dependent reductase (FDR) partners. Feeding authentic biosynthetic intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Note: During the review process of this manuscript, Guth et al reported reconstitution of the activity of JerP and JerO by extensive optimisation of the whole-cell biotransformation conditions in E. coli , similar conversion of jerangolid H to jerangolid A was observed. 39 …”
Section: Resultsmentioning
confidence: 99%
“…Note: During the review process of this manuscript, Guth et al reported reconstitution of the activity of JerP and JerO by extensive optimisation of the whole-cell biotransformation conditions in E. coli , similar conversion of jerangolid H to jerangolid A was observed. 39 …”
Section: Resultsmentioning
confidence: 99%